Bunuel wrote:
If \(\frac{(5x^2 + 65x + 60)}{(x^2 +10x - 24)} = \frac{(5x + 5)}{(x - 2)}\), then which of the following are possible values of x?
A. −60
B. −12
C. −1
D. 1
E. 2
F. 5
Here the equation can be written as-
\(\frac{5(x^2 + 13x + 12)}{(x^2 +10x - 24)} = \frac{5(x + 1)}{(x - 2)}\)
or \(\frac{(x^2 + 13x + 12)}{(x^2 +10x - 24)} = \frac{(x + 1)}{(x - 2)}\)
or \(\frac{(x + 12)(x+1)}{(x + 12)(x-2)} = \frac{(x + 1)}{(x - 2)}\)
or \(\frac{(x+1)}{(x-2)} = \frac{(x + 1)}{(x - 2)}\).
Now looking at the values we notice only when x=2, the equation is not possible, reset all are the possible values.